Changes of peripheral blood immune cells in acute coronary syndrome. (May 2019) - Zhang, Chengxin; Liu, Haiyuan; Wang, Huiping; Tao, Qianshan; Lin, Xianhe; Ge, Shenglin; Zhai, Zhimin
The objective of this study is to explore changes in main immune cells during acute coronary syndrome (ACS), including changes in subsets of monocytes, T cells, and inhibitory myeloid-derived suppressor cells (MDSCs), and to evaluate possible mechanisms. A total of 50 patients suffering from ACS were divided into two subgroups based on attacks of acute infarction, acute myocardial infarction (AMI) with infarction including ST-segment elevation myocardial infarction (STEMI), non-ST-segment elevation myocardial infarction (NSTEMI), and unstable angina (UA). Third, the subgroup of 19 healthy subjects was labeled the normal group (NG). CD14, CD16, and CD45 were used as markers of the subset of monocytes. CD4, CD8, and CD3 were used as markers of the subset of T cells and CD14, human leukocyte antigen—DR isotype (HLA-DR), and CD45 were used as markers of inhibitory MDSCs. Both CD11b + CD206 + and CD11b + CD68 + cells were also assayed. Our data indicated that lymphocytes/karyocytes and monocytes/karyocytes as well as those of CD3 + CD4 + T cells, CD14 + CD16 – monocytes, CD14 + CD16 + monocytes, and CD11b + CD68 + monocytes were significant in all three groups ( P  < 0.05). The ratio of T-cell subtypes to total lymphocytes among the three subgroups can be represented as AMI > UA > NG ( P  < 0.05). The ratios of CD14 + monocytes to total karyocytes among the three subgroups can be represented as NG > UA > AMI ( P  < 0.05). The ratios of CD14 + CD16 – monocytes to total karyocytes among the three subgroups can be represented as NG > UA > AMI ( P  < 0.05). The ratios of CD14 + CD16 + monocytes to total karyocytes among the three subgroups can be represented as AMI > UA > NG ( P  < 0.05). There were no significant differences in the proportion of MDSCs ( P  > 0.05). Certain subsets of monocytes are closely associated with ACS, of which CD14 + CD16 – monocytes present a negative association, while CD14 + CD16 + monocytes show a positive association. In addition, adaptive immunity is associated with unstable plaques of ACS, and CD3 + CD4 + T cells may play a role in early stages of ACS.